2005
DOI: 10.1213/01.ane.0000180200.11626.8e
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Analgesia with Gabapentin and Local Anesthetics Prevents Acute and Chronic Pain After Breast Surgery for Cancer

Abstract: We evaluated the effect of multimodal analgesia on acute and chronic pain after breast surgery for cancer. Fifty patients scheduled for breast cancer surgery were blindly randomized to receive gabapentin, eutectic mixture of local anesthetics cream, and ropivacaine in the wound or three placebos. Pain (visual analog scale) and analgesics were recorded in the postanesthesia care unit (PACU) 3, 6, and 9 h and 8 days after surgery. Three and 6 mo later, patients were assessed for chronic pain. The treatment group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(100 citation statements)
references
References 15 publications
3
96
0
1
Order By: Relevance
“…141,142 Since one of the primary goals of TKA is to improve physical function, this provides an ideal model to study the effects of gabapentin on functional outcomes. While many trials have demonstrated reductions in movement-induced post-surgical pain, 113,116,118,121,127,130,132 whether this reduction translates into accelerated recovery and/or improved functional outcomes remains unknown. Future trials must evaluate the effects of gabapentin and pregabalin on recovery following TJA within the context of multi-modal analgesia.…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…141,142 Since one of the primary goals of TKA is to improve physical function, this provides an ideal model to study the effects of gabapentin on functional outcomes. While many trials have demonstrated reductions in movement-induced post-surgical pain, 113,116,118,121,127,130,132 whether this reduction translates into accelerated recovery and/or improved functional outcomes remains unknown. Future trials must evaluate the effects of gabapentin and pregabalin on recovery following TJA within the context of multi-modal analgesia.…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…Fassoulaki and colleagues published two randomized controlled studies of perioperative gabapentin [42,43]. In the first [42], women received gabapentin 1200 mg per day (400 mg three times a day), starting the evening before surgery, or mexiletine 600 mg per day (200 mg three times per day) or placebo three times per day.…”
Section: Breast Surgerymentioning
confidence: 99%
“…There were no significant differences in pain prevalence or intensity, or in analgesic requirement at 3 months follow-up, although the character of the pain in the control group tended to be burning rather than throbbing, aching or stabbing. In the second study [43], women undergoing breast cancer surgery received a combination of gabapentin 1600 mg per day (400 mg four times a day) for 10 days starting the evening before surgery, plus EMLA cream (20 g) for 3 days starting the day of surgery, plus intraoperative irrigation of the brachial plexus with 10 ml of 0.75% ropivacaine. The control group underwent placebo administration of each of the interventions.…”
Section: Breast Surgerymentioning
confidence: 99%
“…Certaines molécules ont montré leur efficacité dans la prévention de la douleur chronique postopératoire. Il s'agit essentiellement des antiépileptiques gabapentinoïdes (gabapentine [5,10,[11][12][13]24], prégabaline [7]), des antagonistes des récepteurs N-méthyl-D-Aspartate (NMDA)…”
Section: Capsaïcine à Forte Concentrationunclassified